SUTURELESS SCLERAL FIXATION OF INTRAOCULAR LENS IN APHAKIA: CHARACTERISTICS AND VISUAL OUTCOMES - Rahma, Fatkhati Saida; S.W., Firman; W., Tri Wahyu; Supanji, Supanji; Sasongko, M. Bayu (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction & Objective: Sutureless Scleral fixation surgery is one of the secondary intraocular lens (IOL) implantation procedures for aphakic patients with absent or deficient capsular bag support that has gained more attention these days. This study aimed to describe the characteristics, indications for and visual outcomes of the patient who had undergone scleral fixation of intraocular lens at Sardjito Hospital. Methods: A retrospective cross-sectional study of 43 eyes that undergone sutureless scleral fixation intraocular lens at Sardjito Hospital, Yogyakarta. The data were collected from electronic medical records of the patient from October 2020 to December 2022. The data was analysed descriptively by presenting number and percentage for categorical variables and mean ± standard deviation (SD) for numerical variables. Outcome include pre- and postoperative uncorrected visual acuity (UCVA). Results: There were 43 eyes obtained from 40 patients who underwent scleral-fixation intraocular lens in this study, consisting of 35 males (79,55%) and 9 females (20,45%). The mean age of the subjects was 50.04 ± 19.2 years. Lens subluxation was the most of indication for surgery (32,56%), followed by intraocular lens luxation (20,93%), dropped nucleus (16,28%), lens luxation (16,28%), intraocular lens decentration (9,30%), and endophthalmitis (4,65%). Before surgery, most of the patients had visual acuity of less than 3/60 (81,4%) and after surgery, 32,56% had ?6/18, 34,88% had <6/18-6/60 and 18,60% had <6/60-3/60. Conclusion: The characteristics of patient who underwent scleral fixation intraocular lens in Sardjito Hospital was predominantly male and diagnosed with lens subluxation. There were enhancement in visual outcomes.